KINERJA UPTD DALAM PENGELOLAAN OBJEK WISATA CANDI MUARA TAKUS KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Marta Dewi; Zaili Rusli. SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Based on interviews and observations at the resort, there is found a phenomenon that occurs : (a) The main duties of UPTD in resort areaa of Muara Takus Tempel at XIII Koto Kampar has not been done entirely properly, (b) Many programs that have been created by UPTD inresort areas of Muara Takus Tempel was not implemented, (c) The employees in the UPTD is stiil lacking so it is affecting the main duties to be carried out properly. The aim of this study was to determine how the performance of UPTD in resort areas of Muara Takus Tempel at XIII Koto Kampar on this resort management and what are the factors that affect the performance.The locatin method of this study performed in the UPTD office in resort areas of Muara Takus Tempel XIII Koto Kampar ditrict. The primary date source that is stated by Stephen P. Robbins (2001:266), that is (ability), (motivation) and (chance). While secondary data is the data obtained from the UPTD office in resort area of Muara Takus Tempel at XIII Koto Kampar district that is employment data, the data of observation, documentation, review and interviews that conducted and analyzed qualitatively.The results showed that the employee performance of UPTD in resort areas of Muara Takus Temple seen from the ability, motivation, and opportunity, in value is not maximal yet, because there are stiil the man duties that have not been implemetated in conducting employee performance achievement, there are several factors that effect performance include the lack of employees, lack of facilities and infrastucture of its employee, as well as the problem of law levels of education possessed employees.Keywords : Employee performance, Ability, Motivation, Opportunity